Integrated Virtual Reality Learning Framework with Digital Ecosystem for Enhancing Physics Conceptual Understanding - Eko Risdianto; Joselin Santos; Noel Lomerio; Deshinta Arrova Dewi; M. Esad Kuloglu; Sultan Hammad Alshammari; Ressti Nurfitriani (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study develops and evaluates an integrated virtual reality learning framework to improve high school students’ physics conceptual understanding. The framework combines immersive 360° virtual reality videos via Kuula with Google Classroom, ClassPoint, digital flipbooks, and PhET simulations within a problem-based learning environment. Methodology: This study employed a research and development approach using the ADDIE model, combined with a pre-experimental one-group pretest–posttest design. The participants consisted of three cohorts of high school students (n = 115) across different physics topics: Kinematics (n = 36), fluids (n = 39), and particle dynamics (n = 40). The framework was validated by three experts using structured instruments assessing content, media, language, and presentation aspects. Data were collected through validation sheets, student response questionnaires, and conceptual understanding tests. Data analysis included percentage-based measures, N-Gain, Shapiro Wilk tests, paired t-tests, Wilcoxon signed rank tests, and effect size calculations. Main Findings: The results indicate high validity (88.89%–97%) and practicality (86%–98%). The implementation was associated with significant improvements in conceptual understanding, reflected in high N-Gain scores (0.81–0.87) and large effect sizes (p < 0.05). These findings suggest that the integrated virtual reality based learning ecosystem can effectively support conceptual understanding within the studied context. Novelty/Originality of this study: The novelty lies in the systematic integration of the Kuula platform within a multi-component digital learning ecosystem under a problem based learning framework, as well as its application across multiple physics topics to demonstrate consistent learning outcomes.